Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12952-016-0061-0
|View full text |Cite
|
Sign up to set email alerts
|

Dietary phosphate supplement does not rescue skeletal phenotype in a mouse model for craniometaphyseal dysplasia

Abstract: BackgroundMutations in the human progressive ankylosis gene (ANKH; Mus musculus ortholog Ank) have been identified as cause for craniometaphyseal dysplasia (CMD), characterized by progressive thickening of craniofacial bones and flared metaphyses of long bones. We previously reported a knock-in (KI) mouse model (Ank KI/KI) for CMD and showed transiently lower serum phosphate (Pi) as well as significantly higher mRNA levels of fibroblast growth factor 23 (Fgf23) in Ank KI/KI mice. FGF23 is secreted by bone and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Hypoproteinemia is treated with exogenous human albumin infusions for symptomatic support, according to previous results; nevertheless, albumin is costly (17). There are also certain infusion issues that result in albumin loss, despite the fact that the overall time spent maintaining plasma protein after infusion is minimal (18). As a result, it is unable to effectively treat hypoproteinemia and malnutrition in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoproteinemia is treated with exogenous human albumin infusions for symptomatic support, according to previous results; nevertheless, albumin is costly (17). There are also certain infusion issues that result in albumin loss, despite the fact that the overall time spent maintaining plasma protein after infusion is minimal (18). As a result, it is unable to effectively treat hypoproteinemia and malnutrition in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings have shown that hypoproteinemia is treated by the infusion of exogenous human albumin for symptomatic support treatment; however, albumin is expensive ( 10 ). Additionally, there are certain infusion complications, leading to loss of albumin while the total time of maintaining plasma protein after infusion is short ( 11 ). Therefore, it cannot fundamentally correct the hypoproteinemia and malnutrition of the body.…”
Section: Discussionmentioning
confidence: 99%
“…( 5 ) Although Ank KI/KI mice showed a tendency of decreased serum Pi, the difference was not statistically significant in comparison to Ank +/+ mice. ( 10 ) Other Pi regulating hormones such as PTH, 25‐OHD, and intact and cleaved FGF23, were unexpectedly normal in the CMD mouse model as well as in patients with CMD. ( 11 ) Ank KI/KI mice have reduced osteoblastogenesis.…”
Section: Introductionmentioning
confidence: 98%